Permainan Tradisional Edukatif Ã¢â‚¬Å“MpaÃƒÂ¡ NcimiÃ¢â‚¬Â Sebagai Metode Untuk Meningkatkan Kemampuan Motorik Dan Perilaku Sosial Anak - Hardiningsih, Sri; Akbar, Muhammad Rijalul; Nurrahmah, Nurrahmah (Universitas Hamzanwadi, 2020)
In stimulating a child's motor development, both fine and gross motor skills can use games. Games in learning for children can also foster pleasure, happiness and develop social behavior. Research on the